Influence of various preparation methods on percolation behavior of systems based on cross-linked polyurethanes and carbon nanotubes - Lysenkov, E.A.; Lobko, E.V.; Klepko, V.V.; Lysenkova, I.P. (Functional Materials, 2018)
The features of conductivity and percolation behavior of systems based on cross-linked polyurethanes (CPU) and carbon nanotubes (CNT) depending on the preparation methods are studied by methods of impedance spectroscopy and optical microscopy. It is established, that introduction of nanosized laponite in the CPU-CNTs system leads to decrease of the percolation threshold more than three times. The introduction of laponite influences on the size of CNT aggregates, state of their dispersion and spatial distribution homogeneity. The most efficient method of the properties improvement is formation of the CPU-CNTs system under action of direct current (dc) electric field. For the systems, which are formed under the action of dc electric field the percolation threshold decreases more than five times.